Prevalence and prognostic implications of discordant grading and flow-gradient patterns in moderate aortic stenosis. (3rd October 2022) - Stassen, J; Ewe, S; Singh, G K; Amanullah, M R; Hirasawa, K; Butcher, S; Sin, K Y K; Ding, Z P; Sia, C H; Chew, N W S; Kong, W K F; Poh, K K; et al.
Abstract: Background: The prognostic implications of discordant grading in severe aortic stenosis (AS) are well known. However, the prevalence of different flow-gradient patterns and their prognostic implications in moderate AS are unknown. Purpose: To investigate the occurrence and prognostic implications of different flow-gradient patterns in patients with moderate AS. Methods: Patients with moderate AS (aortic valve area 1.0–1.5 cm 2 ) were divided in 4 groups, based on transvalvular mean gradient (MG), stroke volume index (SVi) and left ventricular ejection fraction (LVEF): concordant moderate AS (MG ≥20 mmHg); normal-flow, low-gradient discordant moderate AS (MG <20 mmHg, SVi ≥35 ml/m 2 ); "classical" low-flow, low-gradient discordant moderate AS (MG <20 mmHg, SVi <35 ml/m 2 and LVEF <50%) and "paradoxical" low-flow, low-gradient discordant moderate AS (MG <20 mmHg, SVi <35 ml/m 2 and LVEF ≥50%). The primary endpoint was all-cause mortality. Results: Of 1974 patients (age 73±10 years, 51% men) with moderate AS, 788 (40%) had discordant grading. Patients with discordant grading showed significantly higher mortality rates than patients with concordant grading (p<0.001), even in the subgroup of patients having preserved LVEF (p=0.028) or preserved SVi (p=0.002). Of the patients with discordant grading, 71% had normal-flow, low-gradient moderate AS, 14% had "classical" low-flow, low-gradient moderate AS, and 14% had "paradoxical" low-flow, low-gradient moderate AS (Figure 1). Patients with normal-flow, low-gradient moderate AS, "classical" low-flow, low-gradient moderate AS, and "paradoxical" low-flow, low-gradient moderate AS had worse survival rates than patients with concordant grading (p<0.001) (Figure 2). On multivariable analysis "paradoxical" low-flow, low-gradient (HR: 1.533; 95% CI: 1.133–2.075; p=0.006) and "classical" low-flow, low-gradient (HR: 1.926; 95% CI: 1.442–2.572; p<0.001) but not normal-flow, low-gradient moderate AS were independently associated with all-cause mortality. Conclusion: Discordant grading is frequently (40%) observed in patients with moderate AS. Low-flow, low-gradient patterns account for an important proportion of the discordant cases and are associated with increased mortality. These findings underline the need for better phenotyping patients with discordant moderate AS. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): ESC Training Grant App000064741